Colour reception(s): The Narrative of the Exhibition “Colour Revolution: Victorian Art, Fashion and Design” (Ashmolean Museum, Oxford, 21 September 2023-18 February 2024) - Charlotte Ribeyrol (Sillages Critiques)
This article analyses the aesthetics of reception from the angle of XIXth-century colour. Although the Victorian era is often depicted in sombre tones in popular culture, the age of industry in fact brought about a series of scientific and technical innovations in the fields of colour perception and production. The ERC project CHROMOTOPE analyses the artistic and literary impact of this chromatic turn. One of the major outcomes of this research programme was the exhibition “Colour Revolution : Victorian Art, Fashion and Design” which took place at the Ashmolean Museum, Oxford from 21 September 2023 to 18 February 2024. In this article I shed light on the scenography of this show which explored how the colours of the past might be told to and staged for a modern audience.